Serialização de migrações de máquinas virtuais usando SJF em um ambiente VMWare - Barcelos, André Oshiro (2015)
This work seeks to improve the virtual machines migration process implementing a migration scheduler based on data from a workload characterization in a private cloud. The migrations are necessary to load balancing among hosts, nevertheless they can negatively impact the performance of services. By empirical characterization of the studied cloud, it was observed a large disproportion between the time of a simple migration (shorter time) and a simultaneous one (longer time). Based on these data, it was proposed an algorithm to do the migrations scheduling, in a serial way (removing the simultaneity) and grounded on Shortest Job First. The results of the scheduler showed up better almost in its entirety compared to the VMware, it was possible to decrease 33% in the average time in 93% of the occurred migrations (total of 765 migrations).